1989
DOI: 10.1111/j.1365-3083.1989.tb02466.x
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid from Rheumatoid Arthritis Patients Induces Polyclonal Antibody Formation in Vivo

Abstract: Our previous studies demonstrated the presence of a T-cell replacing factor in the synovial fluid (SF) of patients with rheumatoid arthritis (RA) and that RA-SF can activate, selectively, the induction of IgG2b antibody secreting cells in lipopolysaccharide (LPS)-pretreated mouse spleen cell cultures. In the present study the effect of RA-SF was tested in vivo in mice. Injection of the polyclonal activator LPS induced the production of IgM and IgG3 secreting cells in normal mice. However, the addition of RA-SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In our earlier studies [7,8], we have shown that injection of whole synovial fluid from patients with seropositive RA induces IgGl antibody formation with RF activity in NZ mouse strains (NZB, NZW and (NZB x NZW)F1). but not in mice of MRL/lpr/lpr strain or in normal healthy CBA mice.…”
Section: Introductionmentioning
confidence: 94%
“…In our earlier studies [7,8], we have shown that injection of whole synovial fluid from patients with seropositive RA induces IgGl antibody formation with RF activity in NZ mouse strains (NZB, NZW and (NZB x NZW)F1). but not in mice of MRL/lpr/lpr strain or in normal healthy CBA mice.…”
Section: Introductionmentioning
confidence: 94%
“…Several cytokines, such as interleukin (IL)-1, IL-6, IL-8, IL-10, IL-15, transforming growth factor-b (TGF)-b, tumour necrosis factor-a (TNF)-a, granulocyte-macrophage-colony stimulating factor (GM-CSF) and IgG2b-inducing factor (IgG2bIF) have been found in RA-SF [5][6][7][8][9][10][11][12][13]. IgG2bIF has been shown to selectively induce antibody production of the IgG2b subclass in lipopolysaccharide (LPS)-activated mouse B cells in vitro [13] and in vivo [14]. It is a heparin-binding protein, sensitive to heat and extreme pH values.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were being treated with nonsteroidal antiinflammatory drugs; one also took chloroquine, and another also took sulfasalazine. Samples were handled as previously described (2). Samples of SF were pooled (3-5 per pool) to a volume of 3bSO ml.…”
Section: Methodsmentioning
confidence: 99%
“…This RA SF activity is also a B cell-differentiation factor, which selectively induces IgG2b antibody production by mouse spleen cells in the presence of lipopolysaccharide (LPS) in vitro and in vivo (1,2). Our recent studies have shown that RA SF can also partly reconstitute the B cell defect in inflammation and cartilage destruction, are present in RA SF (7,8).…”
mentioning
confidence: 91%
See 1 more Smart Citation